Analisis peran Analisis Peran dan Kepemimpinan Perempuan di Pondok Pesantren Salafiyah Nurul Huda Poncokusumo Malang - zunita thubatussalamah; Winin Maulidya Saffanah; Nuril Lutfiatul Laila (IAIN Ambon, 2024)
This research examines the role and leadership of women at the Salafiyah Nurul Huda Islamic Boarding School Poncokusumo Malang in the context of gender sociology and gender equality. In general, Islamic boarding schools are often considered as male-dominated institutions, this research shows that women, especially female leaders (Ning), play an important role in the management and education of santri. Through a qualitative approach, data was collected through in-depth interviews and direct observation, which shows that women's leadership is not only limited to administrative functions, but also includes spiritual guidance and character development of students. Despite facing challenges such as male dominance in decision making and gender bias in society, women in this Islamic boarding school show the ability to adapt and contribute significantly. This research provides an overview of the dynamics of women's leadership in the Islamic boarding school environment, as well as its implications for gender equality in Islamic education.